Water Utility and Management Policy for Effective Sharing of Natural Water Resource in the Costal Dry Zone of Sri Lanka in the North East Region - Sivakumar, S. (ENGINEER, Journal of Institution of Engineers Sri Lanka, 2014)
Unlike other natural resources, water is a unique resource, which renews itself. It is due to its constant circulation in the ocean-atmosphere-earth-ocean system. No matter how much water is consumed in daily life, its amount seldom dwindles. With time and under certain conditions water regains its properties and becomes fit for reuse. This is probably the reason why water resources appear to be unlimited for a long time. The North East region of Sri Lanka comprises the whole of eight districts, namely Jaffna, Mannar, Vavuniya, Kilinochchi, Mullaitivu, Trincomalee, Batticaloa, and Ampara and covers an area of 18,881sq.km. The population is around 3.17 million, with growth rate nearly 1.5% per annum. Agriculture, including fisheries, has been the principal economic activity in the province. Over 50% of the total work forces, in the region depend on irrigated agriculture for their livelihood. To accelerate the development and effective utilization of water resource identified within the region, a clearly defined policy formulation is essential. Only with a proper policy for the effective utilization and management of water resource, the expected result can be achieved
Keywords: Water Resource